Designing a Monitoring and Controlling System on IOT-Based Sockets - Yugerita Firmance; Sitti Amalia; Kartiria Kartiria (Faculty of Engineering, Universitas Tanjungpura, 2023)
The government's program to promote energy conservation efforts by reducing the occurrence of vampire power in the surrounding environment, particularly in the household sector. For this reason, modifications are made to the socket so that it can be controlled and monitored remotely through an application on a smartphone. The hardware design uses the NodeMCU ESP8266 V3 as a microcontroller. Combined with the PZEM-004T sensor module to read current, voltage, and power values. Relay module to secure the circuit in case of higher loads. So that in the system, the socket can be monitored 3 sockets simultaneously. While the software design uses the MIT app inventor as the user interface, and the Thingspeak platform as a server. The data is saved in.csv format, which can be opened in Microsoft Excel. The data stored is in the form of the name of the electronic equipment, the time of use, as well as the voltage, current, and power of the device. So that users can manage the use of electrical appliances at home and reduce the occurrence of electric vampires. The test results showed an average voltage error rate of 0.24% with a voltage range of 226 V–230 V, an average current error rate of 22.18%, and an error rate on power of 15.39%. This is caused by the measured load being too small, resulting in higher errors in current and power.